2020
DOI: 10.3390/toxins12050315
|View full text |Cite
|
Sign up to set email alerts
|

High Dosage of Botulinum Toxin Type A in Adult Subjects with Spasticity Following Acquired Central Nervous System Damage: Where Are We at?

Abstract: Spasticity is a common disabling disorder in adult subjects suffering from stroke, brain injury, multiple sclerosis (MS) and spinal cord injury (SCI). Spasticity may be a disabling symptom in people during rehabilitation and botulinum toxin type A (BTX-A) has become the first-line therapy for the local form. High BTX-A doses are often used in clinical practice. Advantages and limitations are debated and the evidence is unclear. Therefore, we analysed the efficacy, safety and evidence for BTX-A high doses. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 76 publications
(146 reference statements)
0
9
0
Order By: Relevance
“…Self-reported pain in CCP is the primary determinator for diminished quality of life [ 4 , 5 ], [ 38 , 39 , 40 ]. In part 1 of this study, we were unable to detect an expected BoNT dose-dependent decrease in spasticity [ 41 , 42 , 43 , 44 , 45 ]. At first glance, this is unexpected because we usually assume a relationship between the dosing of BoNT and modulation/reduction of spasticity.…”
Section: Discussionmentioning
confidence: 77%
“…Self-reported pain in CCP is the primary determinator for diminished quality of life [ 4 , 5 ], [ 38 , 39 , 40 ]. In part 1 of this study, we were unable to detect an expected BoNT dose-dependent decrease in spasticity [ 41 , 42 , 43 , 44 , 45 ]. At first glance, this is unexpected because we usually assume a relationship between the dosing of BoNT and modulation/reduction of spasticity.…”
Section: Discussionmentioning
confidence: 77%
“…Botulinum toxin works by blocking neuromuscular junction transmission, and its effects generally last about 3 months. Dosing of botulinum toxin is done incrementally, and the recommended maximum total dose is 400 units every 3 months, although more recent studies have suggested safety and efficacy with higher dosages 10 . Consensus guidelines are available to help guide dosing based on indication and the targeted muscle 11 …”
Section: Spasticitymentioning
confidence: 99%
“…This can allow patients to visit the hospital less frequently, thus minimizing the risk of exposure to SARS-CoV-2. In the literature, several recent publications suggest that higher incobotulinumtoxinA doses (>400 to 840 units) are safe and well-tolerated [ 22 , 26 , 27 , 28 , 29 ], while others do not rule out increased risks of systemic side effects [ 30 , 31 , 32 , 33 ]. Therefore, dosing has to be considered carefully by the treating physician, on a patient-by-patient basis, and must take into account the previously used dosing levels to assess how many doses could be increased without undue risk.…”
Section: Challenges and Recommendationsmentioning
confidence: 99%